0160 Chemogenetic Activation of Hypothalamic Tachykinin 1-Expressing Neurons Reduces Sleep and Increases Resistance to Isoflurane. (27th May 2020) - Reitz, S; Wasilczuk, A Z; Beh, G; Kelz, M B
Abstract: Introduction: The hypothalamic preoptic area (POA) is a heterogeneous region of the brain, containing intermingled populations of excitatory and inhibitory neurons expressing a wide variety of molecular markers. Of its many important homeostatic roles, the POA modulates arousal including natural states (sleep and wakefulness) as well as drug-induced (anesthetic-induced unconsciousness) states. Although sleep and anesthetic-induced unconsciousness are undoubtedly distinct, multiple lines of evidence demonstrate that shared neuronal circuits regulate both states. Previous work identified a population of sleep-promoting, tachykinin 1-expressing (Tac1) neurons within the POA. Given evidence in the VLPO and SON, we hypothesized that Tac1 POA neurons would be another site of convergence for facilitating entry into both NREM sleep and anesthetic-induced unconsciousness. Methods: Sleep and isoflurane sensitivity were assessed in Tac1-Cre mice expressing either a Cre-dependent excitatory hM3Dq DREADD or a control fluorophore in the POA. Sleep was assessed using beam break actigraphy, while isoflurane sensitivity was assessed using video tracking as well as a loss of righting reflex assay to construct dose-response curves. Results: Unexpectedly, activation of Tac1 POA neurons with 3mg/kg CNO reduced cumulative sleep time by 55% compared to controls (p<0.0001). Decreased sleep time was due to a 59% reduction in sleep bout duration (p<0.01), as the number of sleep bouts remained unchanged. Activity, measured as distance traveled, also increased by 167% compared to vehicle (p<0.0001). Activation of these neurons also increased resistance to isoflurane on both induction (p<0.0001) and emergence (p<0.0001). Additionally, activation during a continuous steady-state exposure to isoflurane destabilized the unconscious state. Conclusion: Our results support the concept that POA Tac1 neurons function as a point of convergence for neural circuits regulating arousal from endogenous and drug-induced states of unconsciousness, while also illustrating the complexity of sleep and wake regulation within the hypothalamus. Support: R01-GM088156-06, T32-HL007953